Perancangan Aplikasi Key Performance Indicator (KPI) Dashboard Berbasis Android Menggunakan React Native dan Backend API Untuk Memantau Kinerja Gudang dan Penjualan Barang Dengan Metode Rapid Application Development (RAD) (Studi Kasus : PT. Mega Dagang In - Supriyadi (Jurnal Penelitian Ilmu komputer, 2023)
In a company, Key Performance Indicator (KPI) is one of the important elements to support the company's operations. KPI is an indicator that can show the performance of a company whether it is in good condition or vice versa. KPIs can be accessed in various ways, one of which is through mobile application media in the form of dashboard. PT. Mega Dagang Internasional is a company engaged in retail. PT. Mega Dagang Internasional currently does not have the KPI dashboard system needed to help the company's operations, especially in the warehouse performance and sales of goods section. PT. Mega Dagang Internasional itself requires an easily accessible KPI system, so the mobile application is the right choice. The data collection method used is the case study method, as well as data collection techniques using observation and interview methods. The application development method itself uses the Rapid Application Development (RAD) method with the stages of needs analysis, application design, development process and gathering feedback, and application implementation or finalization. In order for the implementation of the Rapid Application Development method to be successful, the application development process will use the help of an Android-based mobile application framework, namely React Native.